Primary site as a novel prognostic factor for cardiovascular mortality post-radiotherapy in limited-stage small cell lung cancer: A large population-based study - Zhao, Yuwei; Qin, Fen; Ji, Qingqi; Xia, Wuyan; He, Ben (Frontiers in Cardiovascular Medicine, 2022)
Background The effect of primary site on cardiovascular mortality (CVM) post-radiotherapy (RT) in patients with limited-stage small cell lung cancer (LS-SCLC) remains unclear. Methods We screened the Surveillance, Epidemiology, and End Results (SEER) database between 1988 and 2013. We used cumulative incidence function (CIF) curves to compare CVM incidences, and performed Cox proportional hazards and Fine-Gray competing risk analyses to identify independent risk factors of CVM. Propensity score matching (PSM) analysis was conducted. Results Among enrolled 4,824 patients (median age 57 years old, 49.2% were male), CVM accounts for 10.0% of all deaths after 5 years since cancer diagnosis. Hazard ratios (HRs) for CVM were 1.97 (95% CI: 1.23–3.16, P = 0.005) for main bronchus (MB) patients, 1.65 (95% CI: 1.04–2.63, P = 0.034) for lower lobe (LL) patients and 1.01 (95% CI: 0.40–2.59, P = 0.977) for middle lobe (ML) patients compared to upper lobe (UL) patients. CIF curves showed that the cumulative CVM incidence was greater in the re-categorized MB/LL group compared to UL/ML group both before PSM (P = 0.005) and after PSM (P = 0.012). Multivariate regression models indicated that MB/LL was independently associated with an increased CVM risk, before PSM (HRCox: 1.79, 95% CI: 1.23–2.61, P = 0.002; HRFine−Gray: 1.71, 95% CI: 1.18–2.48, P = 0.005) and after PSM (HRCox: 1.88, 95% CI: 1.20–2.95, P = 0.006; HRFine−Gray: 1.79, 95% CI: 1.15–2.79, P = 0.010). Conclusions MB/LL as the primary site is independently associated with an increased CVM risk post-RT in patients with LS-SCLC.